Comparisons of head impacts between Korean youth athletes and non-athletes in soccer headings - Kim, E.; Kim, Y.-K.; Choi, S. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to quantify the intensity and location of head impacts and compare them between high school soccer athletes and non-athletes. Twenty participants performed five goal-kick and five corner-kick soccer ball headings projected by a ball launcher machine. The head injury criterion (HIC) was calculated from the linear acceleration data from a head-attached inertial measurement unit (IMU) sensor. Results indicated there was no significant difference in HIC between the two groups. The HIC for forehead impacts was significantly lower than those for parietal contact. Coaches need to guide students to perform the forehead header in order to reduce the risk of accumulated head damage.